Phlebotomine sand fly survey, blood meal source identification, and description of Sergentomyia imihra n. sp. in the central Sahara of Algeria - Benallal, Kamal Eddine; Mefissel, Mohammed; Dib, Yassine; Depaquit, Jérôme; Kavan, Daniel; Harrat, Zoubir; Dvořák, Vít; Volf, Petr; Halada, Petr (Parasites & vectors, 2024)
BACKGROUND: Phlebotomine sand flies (Diptera: Psychodidae) are important vectors of various pathogens, mainly Leishmania parasites. In the Old World, the most important genus in term of pathogens transmission is the genus Phlebotomus, which includes many proven or suspected vectors of several Leishmania species, while the genus Sergentomyia remains so far unproven as a vector of human pathogens. Algeria is one of the most affected countries by human leishmaniasis. METHODS: In the present study, an entomological survey was carried out in two provinces, Ghardaïa and Illizi, located in the north and central Sahara, respectively, where cases of human leishmaniasis are recorded. Our goal was to understand the role of the local sand fly species in the transmission of Leishmania parasites and to analyze their blood meal preferences. Collected sand flies were identified by a combination of morphological and molecular approaches that included DNA-barcoding and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) protein profiling. In addition, female blood meals were analyzed by peptide mass mapping using MALDI-TOF MS. RESULTS: In total, 640 sand fly specimens belonging to Phlebotomus and Sergentomyia genera were collected in the two provinces. Sergentomyia antennata and Se. fallax were most abundant species in Ghardaïa, and Ph. papatasi and Ph. alexandri in Illizi. In addition, a new sand fly species was described in Illizi named Sergentomyia (Sergentomyia) imihra n. sp. Blood meal analysis of the engorged females revealed various mammalian hosts, especially goats, but also humans for Phlebotomus papatasi and Ph. alexandri, suggesting that these vector species are opportunistic feeders. CONCLUSIONS: Integrative approach that combined morphological analysis, sequencing of DNA markers, and protein profiling enabled the recognition and description of a new Sergentomyia species, raising the number of the Algerian sand fly fauna to 27 species. Further sand fly surveillance in the central Sahara is recommended to identify the thus-far unknown males of Se. imihra n. sp.
Keywords: kozy; Psychodidae; stravovací zvyklosti; Male; Sergentomyia; Goats; Leishmaniasis; mužské pohlaví; hmyz - vektory; Barcode; Alžírsko; Blood meal; MALDI-TOF mass spectrometry; Animals; lidé; ženské pohlaví; Humans; zvířata; Algeria; Leishmania; Insect Vectors; leishmanióza; Female; Phlebotomus; Feeding Behavior